Preparation, characterization and reduction of burst release of bovine serum albumin (BSA) from biodegradable PLGA microspheres - Rahman, Md. Mokhlesur; Mohamed, Awang; Haliza, Katas; Ansary , Rezaul H. (2014)
In this study, model protein bovine serum albumin (BSA) loaded poly(lactide-co-glycolide) (PLGA) microspheres have been prepared by a conventional water-in-oil-in-water (w/o/w) and a modified water-in-oil-in-oil-in-water (w/o/o/w) double emulsion solvent evaporation method. The prepared microspheres were characterized with respect to their morphology, particle size, encapsulation efficiency, production yield, thermal properties and in vitro drug release. By using w/o/o/w method, a significant decrease in mean particle size and a significant increase in encapsulation efficiency were observed when a binary solvent mixture of ethyl acetate and dichloromethane was used. In w/o/o/w double emulsion solvent evaporation method, the optimized formulation of BSA loaded microspheres was nonporous, smooth-surfaced, and spherical shape under field-emission scanning electron microscope (FE-SEM) with a mean particle size of 3.95 µm and encapsulation efficiency of 98.46%. From 72 days In vitro release studies, microspheres prepared by modified (w/o/o/w) method with a combination of hydroxyl and carboxyl terminated PLGA polymers exhibited a significantly lower initial burst release followed by sustained and almost complete release compared to microspheres prepared by conventional w/o/w technique using a single PLGA polymer. It can be concluded that the modified w/o/o/w method can be proposed as a potential delivery system of therapeutic proteins.